Contractual and Relational Governance Mechanisms in The Power Generation Sector of Pakistan: Adopting Public-Private Partnership Models - Rehman, Muhammad; Habib, Dr. Shahid; Rafique, Dr. Zain (Journal of Professional Research in Social Sciences, 2025)
Public-Private Partnerships (PPPs) are the main element of participatory governance. Since the late 1980s, PPPs have become an essential element in infrastructural development worldwide. In Pakistan, the PPPs approach has contributed to the infrastructural development, especially within the power generation sector. Energy is an essential element of economic growth, and an energy deficit significantly affects progress, impacting the socio-economic development of the country. In this article, the researcher examines the effects of contractual and relational governance mechanisms instead of the principle of governance in the energy sector. Contractual and relational governance mechanisms have different dimensions that make the governance process align with policies and implementation processes. The poor governance mechanism and inefficient policy implementation have negative effects on the energy sector, which becomes the cause of the energy crisis and creates a vacuum for many other problems. PPP models and approaches directly impact the intergovernmental coordination and governance structure. Moreover, the infrastructure of the transmission lines is not capable enough to produce and supplying the maximum demand. The objective of this study is to analyze and evaluate the existing PPP models, governance mechanisms, regulatory framework, and strategies within the power generation sector of Pakistan.